2013
DOI: 10.1590/s1415-790x2013000200019
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas de disfunção sexual em homens com 40 ou mais anos de idade: prevalência e fatores associados

Abstract: Objetivo: O estudo objetivou verificar os fatores associados aos sintomas sexuais do envelhecimento masculino em uma amostra representativa em homens com idade igual ou superior a 40 anos da cidade de Pelotas, RS. Métodos: Foi realizado um estudo transversal de base populacional, incluindo 421 homens que residiam na zona urbana do município. Para avaliar os sintomas sexuais do envelhecimento masculino foi utilizada a dimensão sexual da escala AMS - The Aging Male´s Symptoms Scale . Resultados: A prevalência do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
2
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
(29 reference statements)
0
1
2
4
Order By: Relevance
“…Interesting, age, a recognized variable associated with lower sexual function ( 19 , 20 ) did not show any association in our study. When men aged 18-39 years were compared with those aged 60-69, they presented 2.2 higher risk of erectile dysfunction.…”
Section: Discussioncontrasting
confidence: 74%
“…Interesting, age, a recognized variable associated with lower sexual function ( 19 , 20 ) did not show any association in our study. When men aged 18-39 years were compared with those aged 60-69, they presented 2.2 higher risk of erectile dysfunction.…”
Section: Discussioncontrasting
confidence: 74%
“…Given these results, we observed that the older adults of our study are satisfied with their sexual conduct, which may also be a reflection of the higher prevalence of participants without sexual dysfunction, in contrast to other national and international studies (9,(36)(37)(38) . This divergence may be explained by the variety of instruments available to assess the same construct, but with its own specificities, such as the International Index of Erectile Function (IIEF15) (9) , The Aging Male's Symptoms Scale (AMS) (38) and even questions prepared by the researchers themselves without the use of a validated instrument (36)(37) .…”
Section: Variablescontrasting
confidence: 50%
“…Nevertheless, we emphasize that the sociodemographic characteristic of our sample, especially in relation to high education and, consequently, greater access to sexual information and resources, may have interfered with these results, given the wide availability of strategies and instruments that improve sexual performance. Perhaps the possibility of acquiring these resources is not accessible to male older adults of other investigations, because they have different sociodemographic characteristics from our (38) .…”
Section: Variablesmentioning
confidence: 87%
“…A andropausa ou distúrbio androgênico do envelhecimento masculino (DAEM), é um dos mais importantes e impactantes fenômenos da vida do homem, mais comum a partir de seus 40 anos ou mais, com prevalência de sintomas em 64,3% dos homens (CORRÊA et al, 2013).…”
Section: Introductionunclassified